Définir les centralités commerciales au cœur d’une grande métropole : le cas de Paris intra-muros - Antoine Fleury (Unité Mixte de Recherche 8504 Géographie-cités, 2012)
Since the 1960’s many commercial centres have developed on the outskirts of cities. The significant effects on city centre retailing make it necessary to renew studies in this field. The present article puts forward a methodological approach to define and characterize commercial centres within urban area. On the one hand we aim to examine the relevance of classical models of city centre retailing. On the other hand we aim to point out what happened to the geography of retailing within Inner Paris after three decades of spatial restructuring at the metropolitan level. Results show that the spatial structure of retailing remains very hierarchical. We also find out a series of gradients and a nested hierarchy of centres. Despite the emerging polycentric spatial organisation of city regions, Berry and Davies’ theoretical models appear to remain valid when analyzing city centres retailing.